Product System Families at Rolls‐Royce: A Case Study in Enterprise Transformation. Issue 1 (13th September 2016) - Holt, Jonathan; Brown, David; Walker, Andy
Abstract: This case study describes the initial stages of Product System Families, a project to develop generic, reusable system design artefacts applicable to the complex systems with which Rolls‐Royce equips its aerospace products. Using the example of a gas turbine tip clearance control system, the system thinking behind Product System Families is outlined and the development of the generic artefacts themselves is described, together with the challenges of developing them within the fast‐moving, complex enterprise that is Rolls‐Royce's engineering function. The ultimate aim is to have much of the product design captured in a series of 'house styles' which represent the most advanced, optimized solution and can then be customized quickly and cost‐effectively to specific customer needs.